EFFECT OF CROPPING PATTERN ON THE PROFITABILITY OF LIQUID FERTILIZER USAGE IN DRY SEASON VEGETABLE PRODUCTION IN THE SOUTHERN GUINEA SAVANNAH ZONE OF NIGERIA - Olaghere, Ivie Loretta (Journal of Agricultural Sciences (Belgrade), 2018)
Liquid fertilizer usage in dry season vegetable production is done using different cropping pattern with little or no empirical evidence on which pattern is most profitable. This study therefore investigated the effect of cropping patterns on the profitability of liquid fertilizer usage in dry season vegetable production. Specifically, the study identified the various vegetable enterprises in the study, assessed the inputs and output of the different vegetable enterprises and estimated the profitability of the vegetable enterprises in the study. A multi-stage random sampling procedure was used to select 309 farmers in the Southern Guinea Savannah zone. Pretested and structured interview schedule was used for data collection. Descriptive statistics and partial budgeting techniques were used for data analysis. Twelve different vegetable enterprises were identified in the study. Sixty percent of users of liquid fertilizer cultivated only fruit vegetables such as okra and peppers. Users of both liquid and non-liquid fertilizer on mixed vegetables had the highest quantity of output. However, usage of sole liquid fertilizer on exotic vegetables yielded the highest return to capital invested of 323 percent. The study concluded that usage of liquid fertilizer increases profitability and therefore recommends the formulation and implementation of policies that will foster liquid fertilizer usage.
Keywords: Crop production; Vegetable enterprise; Profitability; Fertilizing; Dry season; Liquid fertilizers